DEDUCTIVE AND INDUCTIVE WAY IN TEACHING GRAMMAR (Konferensiyalar | Conferences, 2024)
This article explores the differences between teaching grammar through inductive and deductive methods. By giving examples, inductive teaching promotes critical thinking and autonomy in learners by allowing them to independently uncover grammar rules. Conversely, deductive instruction gives learners clear direction by outlining the rules in advance. Knowing the subtle differences between inductive and deductive methods can help teachers choose the best strategy for teaching grammar based on learner preferences and learning objectives.